From page to playground: Implanting empathy through physical storytelling for kindergarten students - Hertiki Hertiki; Rahmat Setiawan; Lubna Iasya (Universitas Muhammadiyah Malang, 2025)
Empathy is a crucial component of early childhood education, fostering moral and emotional development. Storytelling, particularly physical storytelling, serves as an effective medium for instilling ethical values in young learners. This study explores kindergarten teachers’ perceptions of physical storytelling as a tool to teach empathy. It focuses on teachers' observations after students performed self-composed stories, including The Lion and the Mouse, The Dog and His Shadow, and The Elephant and His Friends, all of which convey empathy as a moral lesson. Using a qualitative case study approach, data were collected through participatory observation and in-depth interviews with two kindergarten teachers. Thematic analysis was applied to identify key findings. The results indicate that: (1) physical storytelling enhances children's ability to understand and express empathy effectively; (2) teachers anticipate behavioral changes in children, expecting them to exhibit empathetic actions such as sharing, helping, and recognizing their peers' emotions; and (3) storyteller figures, including teachers and peers, play a significant role in shaping children's moral development, as children tend to admire and imitate those who model positive behavior. These findings highlight the importance of interactive storytelling in strengthening children's social-emotional skills. By integrating physical storytelling into early education, teachers can create a more engaging and impactful learning experience, fostering empathy and moral growth in young learners.